The impact of the COVID-19 lockdown on elite sportswomen - Bowes, A.; Lomax, L.; Piasecki, J. (Managing Sport and Leisure, 2020)
Research question: The COVID-19 pandemic decimated elite level sport across the globe, although there were concerns that this impact affected women's sport much more so than for men`s sport. This research considers the impact of the enforced global lockdown on elite women athletes, examining the immediate effect on their training practices, welfare and financial situation.